2016
DOI: 10.1039/c6ra00103c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of laccases immobilized on magnetic nanoparticles and their application as a recyclable nanobiocatalyst for the aerobic oxidation of alcohols in the presence of TEMPO

Abstract: MNPs-Laccase as a novel magnetically recyclable nanobiocatalyst has been used for the selective aerobic oxidation of alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Therefore, in this work, we report on a novel procedure that involves the functionalization of magnetic graphene oxide (Fe 3 O 4 /GO) with APTES and post-modification with glutaraldehyde, which was used as a spacer. It should be noted that this is a continuation of our previous studies on the preparation and application of magnetically recyclable nanobiocatalysts [42,43], In this particular work, we report, for the first time, the preparation of the Fe 3 O 4 -graphene oxide nanocomposite by a facile in situ co-precipitation method that was successfully utilized as a support for the immobilization of laccase (Lac/Fe 3 O 4 /GO). Subsequently, it has been employed as a recyclable catalyst for the synthesis of sulfonamide derivatives in good yields via aerobic oxidative coupling of 2,3-dihydrophthalazine-1,4-dione in the presence of sodium benzenesulfinates using air as an oxidant at room temperature (Scheme 1).…”
Section: Introductionsupporting
confidence: 57%
“…Therefore, in this work, we report on a novel procedure that involves the functionalization of magnetic graphene oxide (Fe 3 O 4 /GO) with APTES and post-modification with glutaraldehyde, which was used as a spacer. It should be noted that this is a continuation of our previous studies on the preparation and application of magnetically recyclable nanobiocatalysts [42,43], In this particular work, we report, for the first time, the preparation of the Fe 3 O 4 -graphene oxide nanocomposite by a facile in situ co-precipitation method that was successfully utilized as a support for the immobilization of laccase (Lac/Fe 3 O 4 /GO). Subsequently, it has been employed as a recyclable catalyst for the synthesis of sulfonamide derivatives in good yields via aerobic oxidative coupling of 2,3-dihydrophthalazine-1,4-dione in the presence of sodium benzenesulfinates using air as an oxidant at room temperature (Scheme 1).…”
Section: Introductionsupporting
confidence: 57%
“…All complexes apparently showed the same size and shape to each other and to that previously obtained in other works 23,24 even if particles larger than 20 nm have also been reported before. 16 Chitosan beads produced in this study were clear macrospheres that proved to be stable in conditions used in enzymatic assays. The size of wet and dry chitosan beads was of about 2 mm and apparently 1 mm, respectively, by using millimeter paper (data not shown).…”
Section: Resultsmentioning
confidence: 79%
“…Therefore, some chitosanases, lipases, amylases and laccases (among others) have been already immobilized using MNPs and/or CMS with successful results. 11,[14][15][16][17][18] In contrast, most chitinases previously immobilized using both types of supports lost their activity aer being reused in consecutive cycles or no data concerning production and characterization of COS were reported. [19][20][21] Chitinase Chit42 from the fungus Trichoderma harzianum was previously expressed in the yeast Pichia pastoris with about 3 g L À1 of the protein produced in this heterologous system.…”
Section: Introductionmentioning
confidence: 99%
“…[24] In the case of FT-IR spectrum of GA-Pd-AmP-MMCF (Figure 5c), the existence of the C=N stretching vibration at 1662 cm -l clearly proved that free -NH 2 group of Pd-AmP-MMCF reacted with -CHO group glutaraldehyde. [29] Comparing the FT-IR spectra of Pd-Laccase@MMCF and GA-Pd-AmP-MMCF demonstrated that they are quite alike and no indicative peaks for laccase were not distinguished in the FT-IR spectrum of Pd-Laccase@MMCF (Figure 5d). Figure 6 displays the magnetic hysteresis loops of MMCF and Pd-Laccase@MMCF nanoparticles.…”
Section: S C H E M E 3 the Process Of Pd-laccase@mmcf Synthesismentioning
confidence: 99%